Algebra and Trigonometry 10th Edition

Published by Cengage Learning
ISBN 10: 9781337271172
ISBN 13: 978-1-33727-117-2

Chapter 1 - 1.1 - Graphs of Equations - 1.1 Exercises - Page 79: 65



Work Step by Step

The middlepoint between $(3,2)$ and $(-9,-8)$ is the center of the circle: $\frac{(3,2)+(-9,-8)}{2}=(-3,-3)$, that is: $h=-3$, $k=-3$ The distance from the center to an endpoint is the radius: $r=\sqrt {(-3-3)^2+(-3-2)^2}=\sqrt {36+25}=\sqrt {61}$ Equation of a circle: $(x−h)^2+(y−k)^2=r^2$ (standard form) $[x-(-3)]^2+[y-(-3)]^2=(\sqrt {61})^2$ $(x+3)^2+(y+3)^2=61$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.